2009
DOI: 10.2459/jcm.0b013e328329c715
|View full text |Cite
|
Sign up to set email alerts
|

Association of heart rate profile during exercise with the severity of coronary artery disease

Abstract: Altered autonomic nervous system regulation affects heart rate profile, increased resting heart rate, decreased heart rate increment, and decreased heart rate decrement, during exercise and this effect is strongly and independently associated with the severity of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Although there is an association between incompetence and myocardial ischemia 11 , the imbalance between oxygen supply-consumption in incompetent patients would not be so encouraged to the point of developing electrocardiographic abnormalities suggesting ischemia, as typically occurs in competent patients, which would decrease the sensitivity of ST in incompetent patients. In this study, the higher incidence of ST-segment depression was associated with lower odds of HF (OR = 0.58; p = 0.0003), similar to what was described by Cay et al 32 . Maddox et al 33 found ischemia on ECG in only 17% of incompetent patients, and Dresing al 27 , in 52% versus 65% of competent patients.…”
Section: -Specificitysupporting
confidence: 76%
“…Although there is an association between incompetence and myocardial ischemia 11 , the imbalance between oxygen supply-consumption in incompetent patients would not be so encouraged to the point of developing electrocardiographic abnormalities suggesting ischemia, as typically occurs in competent patients, which would decrease the sensitivity of ST in incompetent patients. In this study, the higher incidence of ST-segment depression was associated with lower odds of HF (OR = 0.58; p = 0.0003), similar to what was described by Cay et al 32 . Maddox et al 33 found ischemia on ECG in only 17% of incompetent patients, and Dresing al 27 , in 52% versus 65% of competent patients.…”
Section: -Specificitysupporting
confidence: 76%
“…These factors may have increased the accuracy of regression analysis for prediction of SYNTAX score in our study. RHR is another measure of ANS function, and it was demonstrated that increased RHR, as well as decreased HR increment (maximum HR -RHR before exercise) and decreased HR decrement (maximum HR -RHR after exercise), are associated with the severity of CAD [24]. In another study including patients with SCAD, RHR was an independent predictor of SYNTAX score [25].…”
Section: Discussionmentioning
confidence: 99%
“…In their angiographic studies Çay et al (21), reported HRR has been related with severity of the CAD. We did not confirm our results by using invasive methods.…”
Section: Methodsmentioning
confidence: 97%